Structural brain correlates of adolescent resilience - Burt, Keith B.; Whelan, Robert; Conrod, Patricia J.; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L.W.; Bromberg, Uli; Büchel, Christian; Fauth-Bühler, Mira; Flor, Herta; Galinowski, André; Gallinat, Juergen; et al. (Wiley, 2016)
Background